2020
DOI: 10.3892/etm.2020.9315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inulin in the treatment of irritable bowel syndrome with constipation (Review)

Abstract: At present, irritable bowel syndrome (IBS) is a common medical problem all over the world that implies considerable social burden and high costs. Considering the different pathophysiological pathways, unitary management for IBS is not possible. Of the therapeutic approaches that have been proposed so far, only a few have been demonstrated to have beneficial effects in IBS patients. The implication of gut microbiota in IBS is obvious, similarly to the therapeutic effect of pro-/prebiotics, which is reflected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
1
7
0
2
Order By: Relevance
“…The combination of probiotics and prebiotics, otherwise known as symbiotics, in yoghurts is desirable because it contributes to the prevention of many diseases [ 172 , 173 ]. Moreover, Bărboi et al [ 174 ] demonstrated that inulin changes the composition of the gastrointestinal microflora by regulating the passage of the large intestine among people with intestinal disorders. IBS is a dysfunction caused by dysbiosis of the intestinal microflora that affects people of all ages.…”
Section: Prophylactic and Therapeutic Properties Of Plain Yoghurtsmentioning
confidence: 99%
“…The combination of probiotics and prebiotics, otherwise known as symbiotics, in yoghurts is desirable because it contributes to the prevention of many diseases [ 172 , 173 ]. Moreover, Bărboi et al [ 174 ] demonstrated that inulin changes the composition of the gastrointestinal microflora by regulating the passage of the large intestine among people with intestinal disorders. IBS is a dysfunction caused by dysbiosis of the intestinal microflora that affects people of all ages.…”
Section: Prophylactic and Therapeutic Properties Of Plain Yoghurtsmentioning
confidence: 99%
“…Крім того, бродіння інуліну призводить до збільшення коротколанцюгових жирних кислот і вироблення молочної кислоти, тим самим знижується рН товстої кишки, що може додатково контролювати ріст патогенних бактерій і сприяти захисним властивостям інуліну [30]. На цей час також накопичені дані про вплив інуліну на регуляцію перистальтики й транзиту кишечника, консистенцію і частоту випорожнень, склад і активність мікробіоти кишечника, модуляцію імунної відповіді й засвоєння мінеральних речовин [31]. На сьогодні в клінічній практиці часто застосовуються комбіновані препарати, що містять пробіотичні штами в поєднанні з пребіотичними речовинами (симбіотики).…”
Section: таблиця 1 клінічна шкала дегідратаціїunclassified
“…7 On USG, they appear as hypoechoic, hyperechoic or mixed heterogenic echoic structures, depending on the number and size of the cysts and the degree of fibrosis and often show multiple comet tail sign. 8 On CT, they are seen as irregularly marginated, hypoattenuating lesions with no contrast enhancement. These lesions appear hypointense on T1WI and hyperintense on T2WI, compared to the surrounding liver parenchyma (Figure 1).…”
Section: Biliary Hamartoma (Von Meyenberg Complex (Vmc))mentioning
confidence: 99%
“…These lesions appear hypointense on T1WI and hyperintense on T2WI, compared to the surrounding liver parenchyma (Figure 1). 8 The characteristic imaging findings help in the diagnosis; otherwise, followup imaging or histological confirmation is necessary to distinguish them from liver metastases, microabscesses, diffuse primary hepatocellular carcinoma, biliary cysts and Caroli's disease. 8…”
Section: Biliary Hamartoma (Von Meyenberg Complex (Vmc))mentioning
confidence: 99%